Effect of postpartum depression on exclusive breast-feeding practices in sub-Saharan Africa countries: a systematic review and meta-analysis - Demelash Woldeyohannes; Yohannes Tekalegn; Biniyam Sahiledengle; Dejene Ermias; Tekele Ejajo; Lillian Mwanri (BMC, 2021)
Abstract Background Postpartum depression (PPD) is a serious mood disorder that affects behavioural, physical and mental health of women and newborn after childbirth. Although a wide range of research have been conducted on maternal and infant health outcomes, the effect of postpartum depression on exclusive breastfeeding practices remains ambiguous, and needs addressing. The aim of this study was to assess the effect of postpartum depression on exclusive breast feeding practices in sub-Saharan African countries. Methods PubMed, Google Scholar, Science Direct and Cochrane Library were systematically searched for relevant articles published between 2001 and 2020. STATA version 14 was used to calculate the pooled odd ratio with 95% confidence intervals (95% CI). The DerSimonian and Laird random effects meta-analysis was used to measure the effect of postpartum depression on exclusive breast feeding practices. The heterogeneity and publication bias were assessed by using I2 test statistics and Egger's test, respectively. This review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis. Result A total of 1482 published articles and gray literatures were retrieved from different databases. Additional articles were identified from the reference list of identified reports and articles. After assessment of obtained articles, studies not meeting the inclusion criteria were excluded. Twenty six studies involving 30,021 population met the inclusion criteria were included in this review. In sub Saharan Africa the overall estimated level of postpartum depression was 18.6% (95% CI: 13.8, 23.4). This review found that postpartum depression had no significant effect on exclusive breast feeding practices (OR = 0.46, 95% CI: 0.18, 1.14). Conclusion In Sub Saharan Africa, the prevalence of postpartum depression was lower than the report of World Health Organization for developing Country in 2020. This review reveled that maternal postpartum depression has no significant effect on exclusive breast feeding practices. Thus, the investigators strongly recommend the researchers to conduct primary studies using strong study design in sub-Saharan Africa.